Desain Kurikulum Adaptif Berbasis Teknologi dalam PAI: Analisis Artificial Intelligence, Big Data, dan Cyber-Pedagogy - Indriani; Muradah Koimakie; Nur Adilah; Faradita Nurul Abdillah; Amir Basari Zanki; A. Markarma; Rusdin (Paedagogie, 2026)
This study aims to analyze technology-based adaptive curriculum design in Islamic Religious Education through the integration of artificial intelligence (AI), big data, and cyber-pedagogy. The study employs a library research method with a qualitative approach. The research data were sourced from 25 scientific books and journal articles accredited by SINTA, as well as reputable international journals from 2016-2025. Data collection was conducted through documentary studies and analyzed using content analysis and comparative analysis. The results indicate that AI plays a role in personalizing learning and assessment, big data is used to support data-driven decision-making, while cyber-pedagogy creates more interactive and flexible learning experiences. The integration of these three aspects into the PAI curriculum remains focused on strengthening students’ spiritual, moral, and character values. The study’s conclusion indicates that technology-based adaptive curricula are a vital component in the transformation of Islamic education in the digital age through learning that is more relevant, contextual, and aligned with students’ needs.